Risk of prostate cancer‐specific death in men with baseline metabolic aberrations treated with androgen deprivation therapy for biochemical recurrence. (8th March 2016) - Rudman, Sarah M.; Gray, Kathryn P.; Batista, Julie L.; Pitt, Michael J.; Giovannucci, Edward L.; Harper, Peter G.; Loda, Massimo; Mucci, Lorelei A.; Sweeney, Christopher J.
Abstract : Objectives: To investigate the associations of host metabolic factors and metabolic syndrome on prostate cancer‐specific death (PCSD) and overall survival (OS) in patients treated with androgen deprivation therapy (ADT) for biochemically recurrent disease. Patients and Methods: The analysis included 273 patients with prostate cancer treated with ADT for rising prostate‐specific antigen level after surgery or radiotherapy. Patients were assessed for the presence of diabetes, hypertension, dyslipidaemia and obesity before commencing ADT, and Adult Treatment Panel III criteria were used to assess the presence of the composite diagnosis of metabolic syndrome. A competing risks regression model was used to assess associations of time to PCSD with the metabolic conditions, while a multivariable Cox regression model was used to assess associations of OS with metabolic syndrome and metabolic conditions. Results: During a median follow‐up of 11.6 years, 157 patients (58%) died, of whom 58 (21%) died from prostate cancer. At the start of ADT the median (range) patient age was 74 (46–92) years and the median PSA level was 3.0 ng/mL. Metabolic syndrome was observed in 31% of patients; hypertension (68%) and dyslipidaemia (47%) were the most common metabolic conditions. No association of PCSD and metabolic syndrome status was observed. Patients with hypertension tended to have a higher cumulative incidence of PCSD than those without hypertension (sub‐distribution hazard ratio [HR] 1.59, 95% confidence interval [CI] 0.89, 2.84; P = 0.11) although the difference was not statistically significant. Patients with metabolic syndrome had an increased risk of death from all causes (HR 1.56, 95% CI 1.07, 2.29; P = 0.02) when compared with patients without metabolic syndrome, as did patients with hypertension (HR 1.72, 95% CI 1.18, 2.49; P = 0.004). Conclusions: No association of PCSD and metabolic syndrome was observed in this cohort of men receiving ADT for biochemically recurrent prostate cancer. Metabolic syndrome was associated with an increased risk of death from all causes and a similar effect was also observed for patients with prostate cancer with hypertension alone.